Synergistic Adsorption of MIBC/CTAB Mixture at the Air/Water Interface and Applicability of Gibbs Adsorption Equation - Phan, Chi; Nguyen, Van Cuong; Yusa, S.; Yamada, N. (American Chemical Society, 2014)
The synergistic adsorption of a binary surfactant mixture was investigated by tensiometry and neutron reflectometry. The results directly contradicted the conventional Gibbs adsorption equation. The accompanied molecular simulation demonstrated a multilayer arrangement at the synergic conditions, with three distinctively oriented water layers. The positive synergism can be explained by considering the relationship between water orientation and surface tension, in a similar manner to Langmuir’s proposal in 1920s. In spite of the supporting evidence, the relationship has not been quantified in literature. The molecular orientation and arrangement are not included in the current theoretical framework, which simplifies the adsorbed zone into a single monolayer. A new theoretical framework is needed to properly quantify the interfacial adsorption for the mixed surfactant systems.